Educational disparities in perinatal health in Denmark in the first decade of the 21st century: a register-based cohort study. Issue 11 (8th November 2018) - Bilsteen, Josephine Funck; Andresen, Josefine Bernhard; Mortensen, Laust Hvas; Hansen, Anne Vinkel; Andersen, Anne-Marie Nybo
Abstract : Objective: To investigate socioeconomic differences in six perinatal health outcomes in Denmark in the first decade of the 21st century. Design: A population-based cohort study. Setting: Danish national registries. Participants: A total of 646 829 live born children and 3076 stillborn children (≥22+0 weeks of gestation) born in Denmark from 2000 to 2009. We excluded children with implausible relations between birth weight and gestational age (n=644), children without information on maternal country of origin (n=138) and implausible values of maternal year of birth (n=36). Main outcome measures: We investigated the following perinatal health outcomes: stillbirth, neonatal and postneonatal mortality, small-for-gestational age, preterm birth grated into moderate preterm, very preterm and extremely preterm, and congenital anomalies registered in the first year of life. Results: Maternal educational level was inversely associated with all adverse perinatal outcomes. For all examined outcomes, the risk association displayed a clear gradient across the educational levels. The associations remained after adjustment for maternal age, maternal country of origin and maternal year of birth. Compared with mothers with vocational education, mothers with more than 15 years of education had an adjusted risk ratio for stillbirth of 0.64(95% CI 0.56 to 0.72). The corresponding adjusted risk ratios for neonatal mortality, postneonatal mortality, congenital anomalies, moderate preterm birth and small-for-gestational age were, respectively, 0.79(95% CI 0.67 to 0.93), 0.57(95% CI 0.42 to 0.78), 0.87(95% CI 0.83 to 0.91), 0.80(95% CI 0.77 to 0.83) and 0.83(95% CI 0.81 to 0.85). Conclusion: Substantial educational inequalities in perinatal health were still present in Denmark in the first decade of the 21st century.